Fish trophic structure in a first order stream of the Iguatemi River basin, Upper Paraná River, Brazil - Evaneide Nogueira Lopes; Milza Celi Fedatto Abelha; Valéria Flávia Batista-Silva; Elaine Antoniassi Luiz Kashiwaqui; Dayani Bailly (Acta Scientiarum. Biological Sciences, 2016)
We described the spatial distribution of fish trophic groups in the Água Boa Stream, MS, Brazil. Specimens were caught using electrofishing in the upper, intermediate and lower stretches of the stream, between March and November 2008. We analyzed 415 stomach contents of 24 species. Detritus/sediment and aquatic invertebrates were the main exploited resources. Ordination analysis categorized the species in six trophic groups. Aquatic invertivores showed the highest richness (10 species), followed by detritivores (08 species), omnivores (03 species), terrestrial invertivores (03 species), algivores (02 species) and herbivore (01 species). Three trophic groups occurred in the upper stretch, six in the intermediate and five in the lower. Detritivores, omnivores and algivores showed the highest density, while detritivores and aquatic invertivores presented the highest biomass. Autochthonous resources were particularly important to the studied fish fauna, especially aquatic invertebrates, so, conservation actions reducing the simplification of the habitat by silting and recovering the riparian forest are essential to maintain the ichthyofauna of the Água Boa Stream.